DETERMINING PENALTY FOR ONLINE PROSTITUTE VIEWED FROM FIKIH PERSPECTIVE - Andi Mardika (STIS Nahdlatul Ulama Aceh, 2020)
The main issues of the research is how Fiqh reviews about online prostitution.The main issue will be further formulated in several sub-problems, namely: 1) What is the nature, process and impact of online prostitution transactions?, 2) What is the law of prostitution according to fiqh perspective? to answer these questions, the writer uses the Maqasid al-Syariah approach. The data of this study are primary and secondary data. Then, the data also collected from books that have relevance to the issues discussed. Library research is carried out by studying books and journals related to the writing of this journal. The results showed that: Online prostitution is the transaction or sale of sexual services via the internet or social media to make money or payment. The process of prostitution is usually occurred on the roadside or at the place of prostitution. Indeed, it can be transacted through social media. Some of the impacts caused by prostitution are causing and spreading sexually transmitted diseases (STDs). The most contagious diseases are HIV / AIDS, syphilis and gonorrhea (gonorrhea). It broke a family life, morality, law, and religion. Allah explained in An- Nuur verse 2 that the proper punishment for adulterer. Muhsanperpetrators will be stoned to death while GhairuHuhsan will be given a hundred lashes.